2018
DOI: 10.3390/app8122653
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Power Transfer via Subterahertz-Wave

Abstract: Research on wireless power transmission by a rectenna using millimeter waves and subterahertz waves is gaining attention. It is expected that energy harvesters at high frequencies will be developed for use with future 5 G. High-power wireless power supply to various applications will be possible because of miniaturization of the rectenna. As described herein, we investigate earlier studies of millimeter-wave wireless power supply, selecting and explaining salient examples of millimeter-wave high power wireless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Strongly coupled magnetic resonance, achieved using a tuned intermediate resonator between the transmitter and the receiver, has been demonstrated with high efficiencies at a few meters separation between the coils [16]. [15], coupled magnetic resonance [16], rectennas for UHF WPT [17,18], mmWave, sub-mmWave and THz optical rectennas [19,20].…”
Section: Wpt: the Existing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Strongly coupled magnetic resonance, achieved using a tuned intermediate resonator between the transmitter and the receiver, has been demonstrated with high efficiencies at a few meters separation between the coils [16]. [15], coupled magnetic resonance [16], rectennas for UHF WPT [17,18], mmWave, sub-mmWave and THz optical rectennas [19,20].…”
Section: Wpt: the Existing Approachesmentioning
confidence: 99%
“…Furthermore, this technique allows many receivers to be powered using the same source. At millimeter-wave bands and beyond (THz and infrared) large antenna arrays and nano-rectennas are used in power-beaming applications with power handling capabilities in the kW regime [20].…”
Section: Wpt: the Existing Approachesmentioning
confidence: 99%
“…The research field of wireless power transfer (WPT) has attracted considerable attention due to the novel batteryfree solutions it could enable in many emerging applications across different domains such as infrastructure robotics, Internet of Things (IoT) devices, and sensor networks [1,2]. A lot of results have already been reported for WPT circuits and systems operating in the sub-6 GHz frequency bands such as 433 MHz, 868 MHz, and 2.4 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…The two major requirements of an efficient wireless power transfer system are a high-gain directional antenna and a rectifier circuit with high RF-DC conversion efficiency [2]. A rectenna is the combination of a receive antenna and a rectifier that together form a complete WPT receiver [1,5]. The overall performance of a WPT system directly depends on the overall efficiency of the rectenna [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on near field and low frequency WPT. Due to emerging trends of millimter wave (mmW) communications and rapid development of Internet-of-Things devices and sensor nodes, the WPT has grabbed attention in wireless power charging and battery-free solutions in these emerging applications [1,2]. An efficient wireless power transfer system mainly depends on the efficient rectenna (antenna + rectifier) design and specifically a rectifier circuit with high RF-DC conversion efficiency [2].…”
Section: Introductionmentioning
confidence: 99%